Ethenomedicinal Documentation of Medicinal Plants Used by Tribal Peoples of Nuapada District, Odisha, India - Sahu, Guptanjali; Gardia, Debashish; Mishra, Akshya Kumar (Journal for Research in Applied Sciences and Biotechnology, 2022)
The study of a region's plants and their practical applications using the traditions and local knowledge is known as ethnobotany. People have used plants for medical purposes since well before the prehistoric era. On several fronts, traditional medical systems are still heavily utilized. the process of producing medications from plants to treat a variety of human diseases. The native plants and plant parts used as medicines by traditional healers in Nuapada areas are extremely little known. The goal of this research is to compile a list of the exact plant components that local traditional healers in the chosen Nuapada areas utilize to treat a variety of illnesses. The tribes of Nuapada treat their common sickness with 18 species from 14 families.